The Effect of Accessibility, Digitalization, and Business Location on Traders’ Income at the Ubud Thematic Market - Haudija Amalia Wijaya; Anak Agung Ketut Ayuningsasi (Harmony Management: International Journal of Management Science and Business, 2025)
The Ubud Thematic Market is one of the traditional markets that serves as both an economic hub and a tourist destination in Gianyar Regency, Bali Province. This market not only functions as a place for buying and selling transactions but also as a platform for the development of micro-enterprises and the promotion of local culture. However, not all traders have experienced optimal income growth, making it necessary to identify the factors that influence it. This study aims to analyze the effect of accessibility, digitalization, and business location on traders’ income at the Ubud Thematic Market. A quantitative approach was employed, using a survey method through questionnaires distributed to 100 respondents who are active traders at the market. The collected data were analyzed using multiple linear regression analysis to examine the extent to which the independent variables affect traders’ income as the dependent variable. The results show that simultaneously, accessibility, digitalization, and business location have a positive and significant effect on traders’ income at the Ubud Thematic Market. Furthermore, partially, each variable also demonstrates a positive and significant effect on traders’ income. Therefore, market development strategies should not focus solely on one aspect but rather optimize the three factors in an integrated manner to achieve more optimal and sustainable outcomes.